Sharing and discussing sports injury narratives with elite athletes: reflecting on member reflections - Everard, C.; Wadey, R.; Howells, K. (Qualitative Research in Sport, Exercise and Health, 2023)
While the notion of creating and sharing multiple narratives in sport, exercise, and health settings to promote a more diverse landscape is often discussed, the process of, and tensions in doing so are less articulated. Extending a previous study that identified the narrative typologies that scaffold elite athletes` stories of sports injury experiences , the aim of this study was to critically reflect (i.e. introspective, intersubjective), on member reflections with participants to understand how these storylines were received and interpreted. Data was analysed using a reflexive thematic analysis. Using narrative theory as a theoretical lens , five reflexive themes were identified: (a) confronting the dominant narrative, (b) embracing new materialism, (c) extending boundaries of tellability, (d) linear and polyphonic narratives, and (e) symbolic violence. This study provides evidence of how the process of member reflections can enrich and extend our theoretical understandings and offers considerations about how to shift our social and cultural worlds to become more inclusive and diverse.